2011
DOI: 10.1007/s12237-011-9460-0
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Salinity and Light Availability on Abundance and Distribution of Tidal Freshwater and Oligohaline Submersed Aquatic Vegetation

Abstract: Submersed aquatic vegetation (SAV) communities have undergone declines worldwide, exposing them to invasions from non-native species. Over the past decade, the invasive species Hydrilla verticillata has been documented in several tributaries of the lower Chesapeake Bay, Virginia. We used annual aerial mapping surveys from 1998 to 2007, integrated with spatial analyses of water quality data, to analyze the patterns and rates of change of a H. verticillata-dominated SAV community and relate them to varying salin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Our findings suggest that hydrilla invasiveness may be weakened by saltwater intrusion, particularly if this exposure occurs in conjunction with a seasonal period of low production. This hypothesis is supported by observations in the lower Chesapeake Bay system, where periodic salinity intrusions combined with low productivity conditions during the critical early growing season led to subsequent declines in hydrilla dominance (Shields et al, 2012). However, if competitive interactions prior to a salinity intrusion resulted in hydrilla vastly outcompeting wild celery shoots for resources, both species may become overstressed by salinity exposure and decline.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Our findings suggest that hydrilla invasiveness may be weakened by saltwater intrusion, particularly if this exposure occurs in conjunction with a seasonal period of low production. This hypothesis is supported by observations in the lower Chesapeake Bay system, where periodic salinity intrusions combined with low productivity conditions during the critical early growing season led to subsequent declines in hydrilla dominance (Shields et al, 2012). However, if competitive interactions prior to a salinity intrusion resulted in hydrilla vastly outcompeting wild celery shoots for resources, both species may become overstressed by salinity exposure and decline.…”
Section: Discussionmentioning
confidence: 61%
“…A caveat to our speculation is that both the hydrilla and wild celery shoots used in this study originated from lakes that do not experience saltwater intrusion, and that plants from habitats that are subjected to occasional salinity encroachment may have a higher salinity tolerance threshold. Unlike the consistent reports of salinity limitations for the North American invasive strain of hydrilla (Haller et al, 1974; Hillmann et al, 2019; Shields et al, 2012; Twilley & Barko, 1990), reported tolerance thresholds for wild celery have been highly variable in the literature, ranging from as low as approximately 6.6 (Haller et al, 1974) up to salinities greater than 15 (Kraemer et al, 1999), suggesting wide physiological variability in salinity tolerance thresholds among wild celery populations. In this study, salinity treatments for both wild celery and hydrilla showed declines in production and shoot size in addition to shifted biomass allocation strategies, suggesting impacts to production capabilities or soluble carbohydrate reserves (Kraemer et al, 1999; Madsen & Owens, 1998).…”
Section: Discussionmentioning
confidence: 78%
“…A. Middleton, personal observation). Thus, hurricane salinity intrusion could contribute to long‐term change (Hayden et al, 1991) in coastal wetlands, especially because of the differential effects of salinity on regeneration (this study, Baldwin et al, 1996) and vegetation composition (Williams, 1993; Conner, 1995; Stanturf et al, 2007; Hoeppner et al, 2008; Shields et al, 2011; Werner et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…A. Middleton, personal observation). Thus, hurricane salinity intrusion could contribute to long-term change ( Hayden et al, 1991 ) in coastal wetlands, especially because of the diff erential eff ects of salinity on regeneration (this study, Baldwin et al, 1996 ) and vegetation composition ( Williams, 1993 ;Conner, 1995 ;Stanturf et al, 2007 ;Hoeppner et al, 2008 ;Shields et al, 2011 ;Werner et al, 2013 ).…”
Section: Regeneration In Post-hurricane Environ-mentioning
confidence: 94%